2014
DOI: 10.1063/1.4874696
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-solid and solid-solid phase transition of monolayer water: High-density rhombic monolayer ice

Abstract: Liquid-solid and solid-solid phase transitions of a monolayer water confined between two parallel hydrophobic surfaces are studied by molecular dynamics simulations. The solid phase considered is the high-density rhombic monolayer ice. Based on the computed free energy surface, it is found that at a certain width of the slit nanopore, the monolayer water exhibits not only a high freezing point but also a low energy barrier to crystallization. Moreover, through analyzing the oxygen-hydrogen-oxygen angle distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 30 publications
2
33
1
Order By: Relevance
“…Such ice structures were also found in other simulation studies of TIP4P water but confined between other hydrophobic surfaces [44]. In contrast to our results, nearly square ice was also detected in TIP5P simulations, however, for lower temperature and pressure [75].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Such ice structures were also found in other simulation studies of TIP4P water but confined between other hydrophobic surfaces [44]. In contrast to our results, nearly square ice was also detected in TIP5P simulations, however, for lower temperature and pressure [75].…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, such comparisons are hampered by different values for the pressure, temperature and the graphene slit width, as well as different assumptions for the water-graphene interaction. One should keep in mind that our potential energy function, based on high-level electronic structure calculations [82,83], is less hydrophobic and more anisotropic than in most calculations found in the literature [22,44,62,64,71,75]. The experimental evidence of square monolayer ice is of key importance, see Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Puckered monolayer ice can be formed when the width of the silt pore is slightly larger than that giving the flat monolayer ice. 12,27,28 The degree of puckering of the monolayer ice is closely related to the lateral pressure. Numerous bilayer ice polymorphous and polyamorphous structures have been shown in hydrophobic slit pores from computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This ordered phase has a net dipole. However many other studies reported a disordered phase with zero net dipole moment [6][7][8] . An external electric field, should in principle, reorient the local dipoles of water.…”
Section: Introductionmentioning
confidence: 99%